An evaluation of the perceptions and behaviours of individual investors in Malaysia towards equity crowdfunding - Abdul Aziz, Aza Izati (2018)
The regulatory framework for equity crowdfunding was introduced in Malaysia in 2015. As at December 2017, approximately RM 33 million has been raised through a total of 37 successful equity crowdfunding campaigns in Malaysia. Notwithstanding its promising prospects, questions however arise as to the true viability of equity crowdfunding in bridging the funding gap that is currently faced by micro, small and medium-sized businesses in Malaysia. This Management Project seeks to explore this question by specifically focusing on the providers of capital in equity crowdfunding, i.e. the individual investors. The primary objective of this Management Project is to evaluate their perceptions and behaviours towards equity crowdfunding, based on their awareness, interests as well as factors that may influence their investment decisions. By evaluating the perceptions and behaviours of individual investors, it is hoped that valuable insights could be gained with respect to the attractiveness of equity crowdfunding as a form of investment and its overall viability as a potential solution in bridging the funding gap faced by micro, small and medium-sized businesses.